УМУМИЙ ЎРТА ТАЪЛИМ МАКТАБЛАРИ ЎҚУВЧИЛАРИГА МИЛЛИЙ ҲУНАРМАНДЧИЛИКНИ ЎРГАТИШНИНГ ТАРБИЯВИЙ ИМКОНИЯТЛАРИ - Айтмуратов, Б.Т. (SCIENCE and SOCIETY, 2022)
This article researches about the psychological and pedagogical potential of secondary schools learners in search of handicraft through the prism of didactic principles, requirements and measures.
Keywords: global; lifelong education; handicraft; process; method; quality; education; upbringing; performance; qualification; combination; conversation; problem; degree; art; advice; society